Secondary HLH Case Report Highlighting Clinical Challenges - Riad El Fakih; Said Y. Mohamed; Randa Alnounou; Ghada Elgohary (Case Reports in Hematology)
A 19-year-old patient with relapsed acute myeloid leukemia (AML) developed severe and prolonged cytopenia and unexplained jaundice and fever after salvage chemotherapy. His workup revealed hemophagocytosis on the bone marrow biopsy. He was treated for HLH (hemophagocytic lymphohistiocytosis) secondary to AML and chemotherapy. The patient died on day 56 after starting his salvage chemotherapy. Unexpectedly, after his death, the microbiology laboratory reported positive mycobacterial growth from a bronchoalveolar lavage (BAL) sample taken during the workup of his fever. This case illustrates the difficulties in the diagnostic workup of HLH to identify triggers in a timely manner so that a targeted and specific therapy can be administered quickly, given the rapid and deadly evolution of the HLH process.